Islamic Education Information and Communication System in The Perspective of The Qur'an - Muizzudin, Moch.; Ilmin Auliya, Haya Yumna; Muamala, Siti; Wahyudin, Agus Novi; Syahid, Ahmad Habibi (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2024)
The system of information and communication in Islamic education in the digital era enables the more effective dissemination of Islamic values. Technology supports interactive learning, but challenges related to information verification still exist. This study integrates the values of the Qur'an to improve the quality of Islamic education and ensure the accuracy of information. Using a qualitative approach and literature review, the study analyzes the concepts of information and communication systems in Surah Al-Kahfi 13, Ali Imran 110, and Al-Hujurat 6 through scholarly journal articles. The results show: QS. Al-Kahfi 13 emphasizes the importance of truth, ethics, and morality in the Islamic education information system. Islamic education should wisely utilize technology to spread correct knowledge, prioritize spiritual values, and encourage positive change. QS. Ali Imran 110 calls for the use of modern technology, such as Qur'an apps and interactive videos, to convey Islamic values in an engaging way. QS. Al-Hujurat 6 highlights the importance of information verification to prevent hoaxes and ensure valid religious information through proper digital literacy.